Diagnostic criteria for acute‐on‐chronic liver failure and related disease conditions in Japan. Issue 5 (19th May 2022) - Mochida, Satoshi; Nakayama, Nobuaki; Terai, Shuji; Yoshiji, Hitoshi; Shimizu, Masahito; Ido, Akio; Inoue, Kazuaki; Genda, Takuya; Takikawa, Yasuhiro; Takami, Taro; Kato, Naoya; Abe, Masanori; et al.
Abstract: The Intractable Hepato‐Biliary Disease Study Group of Japan, sponsored by the Ministry of Health, Labor and Wealth, proposed in 2018 that patients with cirrhosis and a Child‐Pugh score of 5–9 should be diagnosed as having acute‐on‐chronic liver failure (ACLF) when a deterioration of liver function ("serum bilirubin level of 5.0 mg/dl or more" and "prothrombin time value of 40% or less of the standardized values and/or international normalization rates of 1.5 or more") caused by severe liver damage develops within 28 days after an acute insult, including alcohol abuse, bacterial infection, gastrointestinal bleeding, and the exacerbation of underlying liver diseases. Disease severity can be classified into 4 grades depending on the extent of the deterioration in organ functions, including liver, kidney, cerebral, blood coagulation, circulatory and respiratory functions. The Study Group has since performed an annual nationwide survey of patients with ACLF diagnosed according to the proposed diagnostic criteria as well as those with disease conditions related to ACLF. A total of 501 patients, including 183 patients diagnosed as having ACLF, seen between 2017 and 2019 were enrolled, and univariate and multivariate analyses revealed that the proposed diagnostic criteria were useful for identifying cirrhotic patients with an unfavorable outcome following an acute insult. Consequently, the Study Group determined that the proposed diagnostic criteria should be used in both clinical practice and clinical research as formal diagnostic criteria.